2023
DOI: 10.3390/pathogens12040563
|View full text |Cite
|
Sign up to set email alerts
|

Rift Valley Fever Virus Primes Immune Responses in Aedes aegypti Cells

Abstract: The ongoing global emergence of arthropod-borne (arbo) viruses has accelerated research into the interactions of these viruses with the immune systems of their vectors. Only limited information exists on how bunyaviruses, such as Rift Valley fever virus (RVFV), are sensed by mosquito immunity or escape detection. RVFV is a zoonotic phlebovirus (Bunyavirales; Phenuiviridae) of veterinary and human public health and economic importance. We have shown that the infection of mosquitoes with RVFV triggers the activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…This finding differed from studies performed in human cells with CHIKV (Li et al, 2012) and mosquito cells with DENV (Anglero-Rodrıǵuez et al, 2021) where 1 h of poly(I:C) priming was sufficient to reduce virus replication. However, we did observe the (Laureti et al, 2023). It may thus be worthwhile to measure AMP expression after poly(I:C) treatment and virus infection to determine if a similar priming effect is observed when a viral PAMP is used prior to a virus infection.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This finding differed from studies performed in human cells with CHIKV (Li et al, 2012) and mosquito cells with DENV (Anglero-Rodrıǵuez et al, 2021) where 1 h of poly(I:C) priming was sufficient to reduce virus replication. However, we did observe the (Laureti et al, 2023). It may thus be worthwhile to measure AMP expression after poly(I:C) treatment and virus infection to determine if a similar priming effect is observed when a viral PAMP is used prior to a virus infection.…”
Section: Discussionmentioning
confidence: 72%
“…quinquefasciatus mosquitoes at varying timepoints would help identify additional factors that may be involved in an antiviral response. It has also been shown that priming Aag2 cells with Rift Valley fever virus results in higher AMP expression after bacterial challenge than virus infection or bacterial challenge alone ( Laureti et al., 2023 ). It may thus be worthwhile to measure AMP expression after poly(I:C) treatment and virus infection to determine if a similar priming effect is observed when a viral PAMP is used prior to a virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, a recent paper showed that the RVFV infection of Ae. aegypti Aag2 cells can prime immune responses, resulting in increased expression of certain bacterial PRRs and an enhanced response to bacterial challenge [74]. These data indicate that RVFV infection is indeed sensed by the mosquito immune system, resulting in increased IMD pathway sensitivity.…”
Section: The Imd Pathwaymentioning
confidence: 84%
“…To this end, we stimulated mosquito cells with heat-inactivated (HI) E. coli, which is known to result in robust induction of antimicrobial gene expression (35,36). We collected chromatin samples for PROseq at one and four hours post immune challenge (Fig.…”
Section: Dynamic Control Of Host Responses To Bacterial Stimulationmentioning
confidence: 99%